PERANAN GALANITA SEBAGAI ORGANISASI SEPAKBOLA WANITA DALAM MENGEMBANGKAN SEPAKBOLA WANITA DI INDONESIA 1978-1993 - Yunisal, Papat; Rismayanti, Rismayanti (Jurnal Olahraga, 2019)
This article discusses the emergence of women's football in Indonesia and the development of women's football in Indonesia.The research method used to compile this paper is a historical method that has four stages of work, namely heuristic, critical, interpretation and historiography. The concept used in this study is the role and organization of leadership.From this study it can be concluded that the emergence of women's football has made a new history in Indonesia and brought a revival of women as a form of emancipation of women in Indonesia. The existence of women's football has given birth to a movement of women who have been able to grow new seeds in women's football in Indonesia. Entering the 1970s the development of women's football continued to increase, including marked by the establishment of an organization that houses women's football, namely Galanita.